DEPRIVASI RELATIF: RASA KEADILAN DAN KONDISI PSIKOLOGIS BURUH PABRIK - MA, Faturochman (Jurnal Psikologi, 1998)
Indonesian labours are categorized as the poor people or absolutelydeprived. In the recent time, they are not only absolutely poor but also relatively deprived. The most observable indicator of relative deprivation of labour is the protest to the company or their employers. This article elaborates relative deprivation among labours by identifying negative and injustice feelings. The study finds that frustration, bored, sad, and angry are strong indicators of relative deprivation. Furthermore, the study find that relative deprivation amonglabours is attributed to wage-related factors created by the company.